Deregulation as Disempowerment: Dispossessing Local Forest-dwelling Communities in India - Gupta, Smita (Agrarian South: Journal of Political Economy, 2024)
Recent changes in India's Forest Conservation Act and environment impact assessment procedures, already problematic for community rights and environmental conservation, further undermine both. These changes violate other hard-won constitutional and legal
Keywords: Dispossession; Environment Impact Assessment; Forest Rights; Forest Conservation